Determination of Histidine Protonation States in Proteins by Fast Magic Angle Spinning NMR - Zadorozhnyi, Roman; Sarkar, Sucharita; Quinn, Caitlin M.; Zadrozny, Kaneil K.; Ganser-Pornillos, Barbie K.; Pornillos, Owen; Gronenborn, Angela M.; Polenova, Tatyana (Frontiers in Molecular Biosciences, 2021)
Histidine residues play important structural and functional roles in proteins, such as serving as metal-binding ligands, mediating enzyme catalysis, and modulating proton channel activity. Many of these activities are modulated by the ionization state of the imidazole ring. Here we present a fast MAS NMR approach for the determination of protonation and tautomeric states of His at frequencies of 40–62 kHz. The experiments combine 1H detection with selective magnetization inversion techniques and transferred echo double resonance (TEDOR)–based filters, in 2D heteronuclear correlation experiments. We illustrate this approach using microcrystalline assemblies of HIV-1 CACTD-SP1 protein.